Compensatory strategies and feedback of hyolaryngeal excursion for swallow in treatment of swallowing difficulties in parkinsons disease: A case report - Krishnan, Gayathri; N, Swapna; Prasad, Thulasi (Journal of All India Institute of Speech and Hearing, 2013)
Persons with Parkinson’s disease present with symptoms of dysarthria and dysphagia as secondary motor symptoms of the disease (Jankovic, 2008). These symptoms are progressive in nature and require early identification and intervention. The oral and pharyngeal phases of swallowing are affected in the early or middle stages of the disease. Though evidences for various techniques of swallowing therapy exist in literature most clinicians use client oriented combination of techniques for improving the swallowing efficiency. This case report aims in providing evidence to the effectiveness of using a combination of compensatory strategies and feedback of hyolaryngeal excursion using digital acceleromery to improve swallowing efficiency in a client with Parkinson’s plus syndrome. Training, transfer and generalization of treatment goals are also documented and discussed.